Odwoływalność i mówienie nie wprost - Puczyłowski, Tomasz A. (Filozofia Nauki, 2020)
The aim of this article is to defend the thesis that every conversational implication is cancellable. To this end, I propose a precising definition of cancellability and, based on an analysis of examples proposed by Bach (2006) and Carston (2002), introduce the category of indirectly saying that p. I stipulate that person X said indirectly that p iff (i) X did not say (directly) that p, (ii) from what X said and the analytical truths of the language, it follows that p, and (iii) X meant that p. I define cancellability as follows: if the use of sentence S in context C implies proposition P then P is a cancellable part of this act iff there is a sentence S* and a context C* such that (i) S is a proper part of S*, (ii) S follows from S*, and (iii) P is not implied by S* in C*, but assertion of S* is admissible in C*.